A REVIEW ABOUT THE WAY OF STUDY THROUGH TECHNICAL DRAWING EDUCATION MAJOR ON BUILDING EGINEERING’S STUDENT AT CLASS X IN SMK NEGERI 1 TANJUNG RAYA - 598-608 , Beta Sandika (CIVED, 2015)
Abstract This study begun from a reality, that it is important to study about technical drawing on Building Engineering major in SMK Negeri 1 Tanjung Raya. However, the result of student examination on this subject is generally low. Based on this reality, the study is done to know about the factors that affect low result of the student and to reveal the student way of study on its major. The factors include internal and external. One of the internal factors is the way of study. It was a descriptive study. The population was the students at class X on Buildings Engineering on 2014/2015 year, the amounts are 60 students. The instrument of study is made based on Liker-scale. Before collecting the data, there was a trial to know about instrument validity and reliability. The data statistically analyzed by SPSS Program 17.00 version. Based on the result of analyzed data, it is known that the way of study through technical drawing education major student at class X on Building Engineering major in SMK Negeri 1 Tanjung Raya were on enough, less and not good category. Therefore, the students have to apply the way of study effectively and efficiently, and do some aspects on the way of study properly.   Key words :  The way of study , Technical Drawing